AN OVERVIEW OF COLORECTAL CANCER: IMPLICATION OF TWO MEDICINAL PLANTS IN THEIR TREATMENT - JYOTHI BASINI; SIREESHA RAYADURGAM; SWETHA DAKSHINAMURTHY (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Nowadays, cancer is one of the most common diseases in humans. Among all types, colorectal cancer (CRC) is one of the most serious types diagnosed in men after lung and prostate cancer while in women it occupies the second position after breast cancer worldwide. The risk factors such as obesity, sedentary lifestyle, bad nutritional habits (high in fats and proteins), smoking, and progressive aging are the cause of CRC. The acquisition of abnormal mutations leads to a consisting of many different arrangements of events during the tumor development process. Over the years, different approaches have been employed, in the treatment of cancer. These include chemotherapy, radiotherapy, surgery, and immunotherapy. Chemotherapy is routinely used for cancer treatment, but the toxicity of chemotherapeutics on healthy cells of the human body is obvious. This is the reason for discovering the new, natural origin, substances with potential cytostatic effects and less toxic side effects on the healthy cells. Medicinal plants have a special place in the management of cancer. Numerous cancer research studies have been conducted using traditional medicinal plants to discover new therapeutic agents with fewer side effects. In this review, we are describing two medicinal plants such as Actiniopteris radiata (Sw.) Link (Mayurashikha) and Terminalia pallida Brandis (Tella karaka) (endemic plant) which are available immensely in Chittoor District are used till today by the traditional herbal practitioners, tribal people is near to Talakona forest and Ayurvedic people for various diseases and also for CRC.